Рівень білків і імуноглобулінів у крові кролів за пасалурозної інвазії - Дуда, Юлія Вікторівна; Duda, Yuliya; Duda, Y. V.; Duda, J. V.; Duda, Julia; Duda, Y.; Duda, J.; Duda, Yulia; Duda, Yu.; Duda, Yulia V.; Duda, Julia Viktorovna; Duda, Yu. V.; et al. (ННЦ «Інститут експериментальної і клінічної ветеринарної медицини», 2019)
За впливу збудника Passalurus ambiguus у крові кролів, у порівнянні з аналогічними показниками здорових тварин, виявили достовірно високий (p < 0,001) вміст загального протеїну, глобулінів, γ-глобулінів, IgA, IgG, IgM і креатиніну та низькі рівні сечової кислоти та протеїнового коефіцієнту. Істотні зміни цих показників вказують на посилення імунного захисту. The purpose of our work was to determine the influence of Passalurus ambiguus on proteinogram and the level of immunoglobulins in the blood of rabbits. Analog groups of male rabbits of 3–5 months of age were selected for the experiments. Intensity of invasion was determined by the method of the MacMaster. By spectrophotometric method in the blood of animals there was determined: the content of total protein, albumin, globulin fractions, the level of IgA, IgG, IgM — discrete deposition method according to M. Kostina. Rabbits with pasalurosis have different levels of invasion intensity (II): low (II = 276.47 ± 43.33 eggs/g of feces), high (II = 2,446.67 ± 422.11 eggs/g of feces) — II and medium (II = 1,293.75 ± 275.80 eggs/g of feces) — III research groups. We did not find eggs in the control group. The total protein content was significantly (p < 0.001) higher — from 1.38 times to 1.66 times compared with healthy ones, due to an increase in the content of globulins from 2.08 times (p < 0.001) to 2.26 times (p < 0.001), which led to a decrease in the protein ratio from 2.16 times (p < 0.001) to 3.29 times (p < 0.001) in sick animals with different II. We recorded a high content of γ-globulins almost 1.4 times in these animals compared to healthy ones. We observed a high content of β-globulins and α2-globulins by 6.70% and 7.05% (p < 0.01) and 5.15% and 3.99% (p < 0.05) in animals II and III experimental groups in comparison with control group. A decreased level of uric acid from 4.77 times (p < 0.001) to 6.19 times (p < 0.001) in rabbits with passalurosis is probably due to a violation of the process of its formation in the liver against the background of an increase in acid output through the intestines and kidneys. The creatinine level in experimental rabbits was significantly higher in groups I, II, III by 42.64% (p < 0.001), 46.49% (p < 0.001) and 44.42% (p < 0.001), respectively, compared with the control. IgA and IgG levels were high (p < 0.001) in comparison to healthy rabbits: 2.22 and 2.16 times (in animals with low II), 1.51 and 1.85 times (in animals with high II). We observed a significant (p < 0.001) high level of IgM against the control 1.58 times, 1.82 times and 1.70 times, respectively, in groups I, II, III of infected rabbits. The content of total protein, globulins, γ-globulins, IgA, IgG, IgM and creatinine were significantly higher (p < 0.001) in the blood of sick rabbits than healthy ones. We observed significant changes in the proteinogram of rabbits with high levels of II. These changes indicate an increase in the body’s immune defense under the influence of Passalurus ambiguus. We found a decreased level of uric acid and a protein coefficient due to the low percentage of albumin in sick rabbits. This is possibly due to a violation of the process of their formation in the liver against the background of increased output.
Levels of proteins and immunoglobulins in rabbit blood during Рassalurosis
Дуда Юлія Вікторівна https://orcid.org/0000-0003-0892-0402
Keywords: глобуліни; globulins; пасалуроз; рassalurosis; протеїновий обмін; protein metabolism; Passalurus ambiguus; Passalurus ambiguus; альбуміни; albumins